2015
DOI: 10.1039/c5dt00236b
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium amino-bis(phenolato) complexes for the ring-opening polymerization of rac-lactide

Abstract: Magnesium compounds of tetradentate amino-bis(phenolato) ligands, Mg[L1] (1) and Mg[L2] (2) (where [L1] = 2-pyridyl-N,N-bis(2-methylene-4-methoxy-6-tert-butylphenolato), and [L2] = dimethylaminoethylamino-N,N-bis(2-methylene-4-methyl-6-tert-butylphenolato)) were prepared. The proligands, H2[L1] and H2[L2] were reacted with di(n-butyl)magnesium in toluene to give the desired compounds in high yields. Compounds 1 and 2 exhibit dimeric structures in solutions of non-coordinating solvents as observed by NMR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 69 publications
2
34
1
Order By: Relevance
“…Magnesium complexes have also received significant interest in the ROP of LA. [70][71][72][73][74][75][76][77][78][79][80][81][82] Chisholm and co-workers have reported numerous Mg(II)-complexes for the production of heterotactic PLA (P r = 0.90-0.96). 51,[83][84][85] Both Coates et al 50 (Zn(II), P r = 0.94; Mg(II), atactic PLA) and Ma et al 58 (Zn(II), P r = 0.20; Mg(II), P r = 0.81) have previously shown metal exchange to dramatically impact stereocontrol.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium complexes have also received significant interest in the ROP of LA. [70][71][72][73][74][75][76][77][78][79][80][81][82] Chisholm and co-workers have reported numerous Mg(II)-complexes for the production of heterotactic PLA (P r = 0.90-0.96). 51,[83][84][85] Both Coates et al 50 (Zn(II), P r = 0.94; Mg(II), atactic PLA) and Ma et al 58 (Zn(II), P r = 0.20; Mg(II), P r = 0.81) have previously shown metal exchange to dramatically impact stereocontrol.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium complexes have also attracted attention for the ROP of LA. [88][89][90][91][92][93][94][95][96][97][98][99][100] Often, such complexes are isostructural to their Zn(II) analogues. In the case of the β-diiminate Mg(II) complex, the heteroselectivity observed with the Zn(II) analogue was not replicated.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some tin compounds have appreciable cytotoxicity and are susceptible to atmospheric conditions which increase the production expenses . In this regard, research is now exploring the use of other organometallic compounds with lower toxicity such as alkali metals, magnesium, calcium, zinc, copper, iron, and aluminum all of which have shown promising results.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that the ligand used in organometallic complexes can influence polymerization reactions and products, and this is due to ease of modifying the backbone architecture. Prevalent ligand frameworks such as diketiminate, salen and phenolate, have been widely tailored to regulate the steric and electronic properties, thereby affecting catalytic activity of ROP reaction initiators. We recently focused our attention on the opportunity to fine tune formamidine ligands architecture and study their effect on catalytic behaviour in ROP.…”
Section: Introductionmentioning
confidence: 99%